Darwin Koenig letter to James J. Dinsmore regarding birds sighted in summer 1984, July 30, 1984 - Koenig, Darwinet al (1984)
Darwin Koenig letter to James J. Dinsmore was regarding birds sighted in summer 1984, July 30, 1984. He sighted 45 species including five with nests or young. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1984. Epson - sheet feed